Exploring factors that influence digital adoption in the South African oil and gas industry - Zuma, Dumisani (My University, 2022)
The purpose of this research was to provide insight into the factors that impact the adoption of digital tools in the Oil and Gas industry in South Africa, with the focus on digital enterprise resource planning (ERP). The research data for the study was collected by conducting semi-structured interviews with the people who were directly involved with the scoping, designing, implementation and adoption of the digital ERP system in the focal organisation. This was done by way of finding answers to three research questions, which were structured to determine the overall factors affecting adoption, then determining the impact of these factors on the implementation of the ERP system. The Technology Organisation Environment (TOE) conceptual model was used in developing proposed relationships, after which a data modelling and analysis tool Atlas.ti was used to rank the factors. The interview guide was developed in conjunction with the conceptual model and factors for the study identified. The factors identified for the study were confirmed by the existing literature, with some new ones identified through discussion with participating respondents in the interview phase of the study. The study established that all T-O-E aspects are important when implementing the digital ERP in the Oil and Gas industry. One of the important recommendations is that the organisation performs a full assessment before the decision to adopt, making sure that the implementation is supported entirely by the business that will use the tool, and that all other T-O-E aspects are in place.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Enterprise Resource Planning (ERP); Digitalisation; Implementation; Adoption; Data Storage; Technology; Business Process; SDG-8: Decent work and economic growth